Studi tentang Kesejahteraan Petani Karet di Nagari Sungai Batuang, Kecamatan Kamang Baru Kabupaten Sijunjung - Yusmar, Erpis; Iskarni, Paus (TSAQOFAH, 2025)
This study aims to assess the welfare level of rubber farmers in Nagari Sungai Batuang and to analyze the economic, social, and environmental factors influencing their welfare. Employing a mixed methods approach with an explanatory sequential design, the research began with a quantitative survey of 33 rubber farmers, followed by in-depth qualitative interviews with six purposively selected informants based on variations in welfare level, land ownership, access to aid, and social participation. The findings indicate that the farmers’ welfare levels range from low to moderate, with a distribution of 24.2% categorized as pre-prosperous, 39.4% as prosperous I, 27.3% as prosperous II, and 9.1% as prosperous III. The primary income source for farmers is rubber latex sales, contributing an average of 72% of total income, while the remainder derives from side activities such as livestock farming, trading, and freelance work. Multiple linear regression analysis reveals that economic factors have the most significant influence on welfare (β = 0.489; p < 0.001), followed by environmental factors (β = 0.351; p = 0.004) and social factors (β = 0.274; p = 0.038). Qualitative findings highlight key barriers including dependence on fluctuating rubber prices, limited infrastructure, and low institutional participation. Furthermore, farmers’ perceptions of welfare are also shaped by non-material dimensions such as a sense of security, social relationships, and life meaning. The study concludes by emphasizing the need for integrated interventions involving economic capacity building, agricultural infrastructure improvement, institutional strengthening, and social support to enhance welfare in a holistic and sustainable manner.